The Effect of Severe Birth Asphyxia on the Hemostasis System in Newborns During the First Hour of Life - I. E. Golub; A. A. Zarubin; N. I. Micheeva; A. S. Vanyarkina; O. G. Ivanova (Общая реаниматология, 2017)
In newborns with severe intranatal asphyxia, the hemostasis system adaptation is impaired, thus increasing the risk of bleeding during the first day of life.The purpose of the work was to evaluate the effect of severe birth asphyxia and metabolic acidosis on the newborns' hemostasis system, based on the thromboelastography (TEG) findings.Materials and methods. A retrospective analysis of medical records of 40 severely asphyxiated newborns (group 1) and 20 healthy newborns (group 2) was performed. The study was carried out during the first hour of life of the newborns.Results. Infants in group 1 demonstrated a reduced activity of platelets and enzymatic components of the coagulation. The enzymatic phase of the coagulation hemostasis (P<0.001) and the kinetics of clot strength growth significantly decreased in group 1 newborns, as compared to the second group (P<0.001 and P<0.01, respectively). The fibrin network growth rate and its structurization in group 1 newborns was lower than that in group 2 newborns (P<0.05). The platelet activity in group 1 infants was reduced as compared to group 2 (P< 0.05).Fibrinolysis in newborns did not differ at the 30th minute of the study. The correlation analysis demonstrated that decreased pH and Be values and hyperlactacidemia correlated; platelet and coagulation hemostasis parameters were altered with a shift to hypocoagulation. Conclusion. Thromboelastographic study of whole blood samples demonstrated a shift of the hemostatic system to hypocoagulation for both platelet and enzymatic components of hemostasis, without any changes in the clot lysis in severely asphyxiated newborns.